ASSESSMENT OF THE FILTRATION COMPONENT OF THE WATER BALANCE OF LEBEDYNE LAKE (SUMY REGION) - Koshliakov О.; Dyniak О.; Chomko, D.; Koshliakova І. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Quantitative analysis of the relationship between surface and groundwater in the area adjacent to Lebedyne Lake (Sumy region) is presented. Preliminary studies do not explain the role and quantification of groundwater runoff in lake level fluctuations. The solution to the problem is proposed by the authors based on the calculation of water balance. The article presents the results of research of hydrogeological conditions of the territory near the lake and the results of quantitative assessment of the underground component of the water balance. It has been established that the level regime of Lebedyne Lake is determined by meteorological factors, terrain and conditions of interconnection of surface and groundwater (primarily groundwater). It was also found that groundwater in alluvial deposits in the area adjacent to the lake is separated from the aquifers below, a thick layer of waterproof rocks. Therefore, the existing long-term operation of the mentioned aquifers and complexes for the purpose of centralized water supply cannot be a direct cause of changes in the natural water balance of groundwater and lakes. Also, low anthropogenic pressure in the surrounding area cannot be considered a factor that significantly affects the natural water balance. Groundwater supply in the study area is due to infiltration of precipitation and the flow of surface water from the lake into the groundwater. Changing the water level in the lake very quickly leads to a change in the water level in the soil aquifer, and vice versa. According to calculations, the total loss from the lake to groundwater supply is about 207.1 m3 /day or 75600 m3 /year. The obtained results are the basis for scientific substantiation of designing a system of local monitoring of groundwater status in the area adjacent to Lebedyne Lake.